2022
DOI: 10.12688/f1000research.75703.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the knowledge, attitudes and practices of Lebanese shoppers towards food labeling: The first steps in the Nutri-score roadmap

Abstract: Background: Food labeling is a fundamental educational tool for advocating for public awareness. It emphasizes knowledge of the nutrient content of food and thus directs the choice towards the healthiest food products. This cross-sectional survey aimed to assess the knowledge, attitudes, and practices (KAP) regarding nutrition label use in Lebanon through a valid questionnaire. Methods: Overall, 768 participants (mean age: 30.8 ±12, males: 60.2%) were recruited randomly between February and May 2020. We used w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…These findings are consistent with similar research conducted in Lebanon. 24 Access to the Internet is affordable in developing countries, and therefore, users have rapidly grown. 25 Vietnam is among the countries with the most Internet users in Asia.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with similar research conducted in Lebanon. 24 Access to the Internet is affordable in developing countries, and therefore, users have rapidly grown. 25 Vietnam is among the countries with the most Internet users in Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Food labels [ 1 ] provide information on food packaging that helps consumers make informed choices about the food they eat. It is a legal requirement in many countries and typically includes a list of ingredients and nutritional information [ 2 , 3 ] such as the calorie content [ 4 , 5 ], fat [ 6 , 7 ], protein [ 5 , 8 ], and carbohydrate levels [ 9 ], and any specific health claims [ 10 , 11 ] related to the food. The purpose of F&NL is to ensure that consumers have access to accurate and helpful information about the food they buy, which can help them make healthier choices [ 12 ] and manage their diets more effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Food labeling information and consumers' level of education impose a large contribution in ensuring consumers about the good and bad effects of food items which they consumed [1]. Although many studies from the Middle East have explored the subject of consumers' awareness of food labels in different population groups however a study on food labels awareness among health science students in the Aseer region of the Kingdom of Saudi Arabia not much explored [8][9][10][11]. Whereas a study conducted in Riyadh among female students showed the 17.7% frequency of use of food by participants where as 16.8% of respondents never use food labeling before purchasing food items [11].…”
Section: Introductionmentioning
confidence: 99%